QUALITY AND SENSORY ATTRIBUTES OF EGGS FROM DIFFERENT CHICKEN GENOTYPES IN PAKISTAN - J. Hussain; K. Javed; F. Hussnain; S. Musarrat; A. Mahmud; S. Mehmood (Journal of Animal and Plant Sciences, 2018)
This study was conducted with the aim of comparing the quality and sensory attributes of eggs from different chicken genotypes in Pakistan (Fayoumi, White Leghorn, Aseel, Rhode Island Red, Naked Neck, and White Plymouth Rock). For quality analysis, 10 eggs from each chicken genotype were randomly collected and subjected to egg quality analysis. For sensory evaluation, another sample of 10 eggs of each genotype was boiled and presented to a well-trained panel of 20 experts and evaluated on 15 points hedonic scale. The data were analyzed through one-way ANOVA using a completely randomized design and means were compared through Duncans Multiple Range tesut sing SAS 9.4. Eggs of Fayoumi breed showed significantly higher ( Pd0.05) specific gravity, Haugh unit score, and yolk color score as compared to other breeds. Similarly, among different breeds, eggs of Rhode Island Red breed had the highest albumen percentage, while yolk percentage was significantly higher (Pd0.05) in eggs of Aseel, Naked Neck, and Fayoumi breeds. Eggs from White Leghorn hens received the highest ( Pd0.05) sensory ratings regarding yolk and albumen taste, mouthfeel, flavor and overall acceptance. Eggs of Aseel had the lowest ratings for the color of albumen, while, eggs of White Plymouth rock hens had a very strong aroma of albumen. Overall results of the present study suggest that eggs from Fayoumi have better internal quality and White Leghorn have better organoleptic/sensory attributes. and Villeneuve, 1994). The influence of genetics on
Keywords: Chicken genotypes; egg quality; sensory attributes.